Frequency, acceptability, and selection: A case study of clause-embedding. Issue 1 (4th November 2020) - White, Aaron Steven; Rawlins, Kyle
Abstract : We investigate the relationship between the frequency with which verbs are found in particular subcategorization frames and the acceptability of those verbs in those frames, focusing in particular on subordinate clause-taking verbs, such as think, want, and tell . We show that verbs' subcategorization frame frequency distributions are poor predictors of their acceptability in those frames—explaining, at best, less than 1 3 \documentclass[10pt]{article} \usepackage{wasysym} \usepackage[substack]{amsmath} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage[mathscr]{eucal} \usepackage{mathrsfs} \usepackage{pmc} \usepackage[Euler]{upgreek} \pagestyle{empty} \oddsidemargin -1.0in \begin{document} \[ \frac{1}{3} \] \end{document} of the total information about acceptability across the lexicon—and, further, that common matrix factorization techniques used to model the acquisition of verbs' acceptability in subcategorization frames fare only marginally better.